Proposed Marketing Strategies to Increase Product Awareness for Instant Drip Bag Coffee - Ivan Zacky Nugraha; Prawira Fajarindra Belgiawan (Publikasi Indonesia, 2025)
The coffee industry in Indonesia has experienced significant growth, driven by evolving consumer preferences and the increasing popularity of coffee culture. Portacaba Roastery, a Bandung-based coffee company, has established itself as a key supplier of ground coffee to businesses but faces challenges in expanding its market to direct consumers, particularly for its instant drip bag coffee products. This study aims to identify the main causes of low product awareness and develop effective marketing strategies to increase consumer recognition of Portacaba’s instant coffee offerings. Using a qualitative research approach, data collection was conducted through in-depth interviews with stakeholders, including Portacaba's owners and potential customers. The research utilizes Porter’s Five Forces, SWOT analysis, and consumer behavior analysis to evaluate market conditions and competitive positioning. Findings indicate that limited brand awareness, high competition, and a lack of differentiation in marketing approaches hinder the growth of Portacaba’s instant coffee segment. To address these challenges, the study proposes a multi-faceted marketing strategy, including content marketing, social media engagement, influencer partnerships, targeted digital advertising, and customer loyalty programs. By implementing these strategies, Portacaba can strengthen its market presence, enhance consumer engagement, and drive sales of its instant drip bag coffee.